CAUSALITIES OF MOTIVATION, SELF-RELATED BELIEFS, AND STUDENT ENGAGEMENT TOWARDS HIGH SCHOOL STUDENTS’ ACHIEVEMENT USING STRUCTURAL EQUATION MODELING - Riadi, Alexander Joseph; Sukarsa, I Komang Gde; Suciptawati, Ni Luh Putu; Kencana, Eka N (PATTIMURA UNIVERSITY, 2024)
Students’ academic performances is an important factor as it affects students’ chances of higher education and job opportunities. While cognitive factor (e.g., intelligence quotient) plays a major role in students’ performances in academic environment, it does not guarantee students’ academic achievement. Instead, researches shows that non-cognitive factor can affects student performance as well. Three non-cognitive factor that will be researched in this study are motivation, self-related beliefs, and engagement. Using Structural Equation Modeling (SEM) as the method of choice to accommodate the study of the factors. 699 of students’ sample was taken from six public high school in Denpasar to conduct the research. SEM is used for its ability to analyze latent factors using measurement model and its ability to estimate multiple structural relation simultaneously. The model with a Goodness-of-fit (GFI) score of 0.981 confirms that Motivation does significantly directly affects student performances. Self-related beliefs and Engagement on the other hand significantly directly affects Motivation, hence the two constructs significantly indirectly affect student achievement.